Ethnobotanical Study of Traditional Jakun Midwifery Practices: Prenatal and Postnatal Care Treatment - M Durai Raja, Thivenisha; Sabran, Siti Fatimah (Enhanced Knowledge in Sciences and Technology, 2025)
Midwifery practices remain significant in many ethnic groups but are increasingly forgotten in rural areas, particularly among indigenous communities in Malaysia. The Jakun people’s traditional midwifery practices, including the use of herbal plants for prenatal and postnatal care, are at risk of being lost due to modernization and cultural shifts. This study documents the ethnobotanical knowledge and provides an inventory of plant species used by the Jakun community in Kampung Peta, Mersing. Data were gathered through semi-structured interviews, field surveys, and answering questionnaires, documenting 15 plants from 13 families such as Zingiberaceae, Piperaceae, Euphorbiaceae, Vitaceae, Malvaceae, Fabaceae, Musaceae, Annonaceae, Clusiaceae, Lygodiaceae, Acanthaceae, Lauraceae, and Araliaceae. For example, the Leea indica species, are used traditionally in herbal baths to treat body aches and have antibacterial properties, and Panax ginseng’s roots were boiled and made into a decoction, as an herbal drink which has a vital medical function. The findings reveal a rich repository of ethnobotanical knowledge and highlight the urgent need to preserve traditional practices. Future research could explore the potential of these plants for sustainable healthcare solutions and therapeutic development. The findings of this study highlight the rich ethnobotanical knowledge within Jakun traditional midwifery practices, revealing the significant potential for scientific validation of documented plants.